2015
DOI: 10.1177/2347631115584121
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of International Higher Education Students in a Foreign Country

Abstract: Over the last several years, the number of international students attending colleges and universities in Malaysia has increased substantially. While the number of international students pursuing undergraduate and post graduate studies in Malaysian higher education institutions has increased, it is curious that some limitations and challenges exist to these students in their academic life. The main objective of this case study was to explore the challenges of Iranian students, as the largest group of internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Apparently, with growing pressure to complete their thesis within the stipulated time (MOHE, 2016), students in this study tended to prioritise completing their thesis, rather than publishing during their candidature. Financial strain appeared the be the most influential factor in this, with both supervisors and students being mindful of financial pressures, which can cause a lot of stress and anxiety (Khawaja & Stallman, 2011;Khodabandelou et al, 2015;Umar et al, 2014). The dilemma students have between striving for a timely completion and publishing, therefore, needs to be acknowledged by universities and supervisors (Manathunga, 2019), and discussed more explicitly with students.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, with growing pressure to complete their thesis within the stipulated time (MOHE, 2016), students in this study tended to prioritise completing their thesis, rather than publishing during their candidature. Financial strain appeared the be the most influential factor in this, with both supervisors and students being mindful of financial pressures, which can cause a lot of stress and anxiety (Khawaja & Stallman, 2011;Khodabandelou et al, 2015;Umar et al, 2014). The dilemma students have between striving for a timely completion and publishing, therefore, needs to be acknowledged by universities and supervisors (Manathunga, 2019), and discussed more explicitly with students.…”
Section: Discussionmentioning
confidence: 99%
“…She worked part-time but it was still very difficult for her to make both ends meet. Similar problems were experienced by the international students who participated in Khodabandelou et al ’s (2015) study. The researchers described how the economic crisis in Malaysia caused a lot of difficulties for the Iranian international students studying there; some of them had to return home because their parents could not pay for the tuition and living expenses in Malaysia, and the students themselves could not find part-time work in that country because of the government’s restrictions.…”
Section: Findings and Discussionmentioning
confidence: 59%
“…For instance, Poyrazli and Grahame (2007) found that the miscommunication between the host university administration and international students resulted in students’ experiencing difficulties that could have been avoided if the university were more responsive to their students’ circumstances. In a similar vein, Khodabandelou et al (2015) stated that the lack of communication and accurate information about the host university regulations was the main cause of academic challenges the participants in their study encountered. Although Poyrazli and Grahame (2007) and Khodabandelou et al (2015) did not report that the experienced challenges with the administration of the host universities led to the international students’ feeling frustrated and ignored as it happened in my study, we can see that the role of the administration in providing timely information to students and engaging them in the socio-cultural life is very important.…”
Section: Findings and Discussionmentioning
confidence: 98%
“…Tong, Sainsbury and Craig (2007) indicated that qualitative methods have an explorative nature and enable scholars to explore and investigate the intricacy of phenomena happened in the research area. Data collection method in qualitative research design in contrast with quantitative research design leads to a more in-depth understanding of the intended phenomenon (Khodabandelou, Karimi, & Ehsani, 2015). Focus groups have been identified as a special type of group interview that is structured to gather detailed opinions and knowledge about a particular topic from selected participants (Bader & Rossi, 2002, p 6).…”
Section: Methodsmentioning
confidence: 99%